Restoring Mathematics Identities of Black Learners: A Curricular Approach - Gholson, Maisie L.; Robinson, Darrius D. (Theory into practice, 2019)
Black learners are subject to systemic physical, symbolic, and epistemological violence in mathematics classrooms. Such violence has negative ramifications for Black children's mathematics learning and identity development. The authors argue that space should be made within the mathematics classroom to repair the harm caused by this violence. This article describes an identity-based curriculum, Mathematics for Justice, Identity, and meta-Cognition (or MaJIC), that provides a form of mathematics therapy through a restorative justice framework. The Silhouette Activity is highlighted as one approach that allows Black mathematics learners to engage in a restorative process of writing and drawing the internal and external messages they receive as mathematics doers and knowers.